Dietary patterns in infancy and cognitive and neuropsychological function in childhood. - Gale, C; Martyn, C; Marriott, L; Limond, J; Crozier, S; Inskip, H; Godfrey, K; Law, C; Cooper, C; Robinson, S (2009)
BACKGROUND: Trials in developing countries suggest that improving young children's diet may benefit cognitive development. Whether dietary composition influences young children's cognition in developed countries is unclear. Although many studies have examined the relation between type of milk received in infancy and subsequent cognition, there has been no investigation of the possible effect of variations in the weaning diet. METHODS: We studied 241 children aged 4 years, whose diet had been assessed at age 6 and 12 months. We measured IQ with the Wechsler Pre-School and Primary Scale of Intelligence, visual attention, visuomotor precision, sentence repetition and verbal fluency with the Developmental Neuropsychological Assessment (NEPSY), and visual form-constancy with the Test of Visual Perceptual Skills. RESULTS: In sex-adjusted analyses, children whose diet in infancy was characterised by high consumption of fruit, vegetables and home-prepared foods ('infant guidelines' dietary pattern) had higher full-scale and verbal IQ and better memory performance at age 4 years. Further adjustment for maternal education, intelligence, social class, quality of the home environment and other potential confounding factors attenuated these associations but the relations between higher 'infant guidelines' diet score and full-scale and verbal IQ remained significant. For a standard deviation increase in 'infant guidelines' diet score at 6 or 12 months full-scale IQ rose by .18 (95% CI .04 to .31) of a standard deviation. For a standard deviation increase in 'infant guidelines' diet score at 6 months verbal IQ rose by .14 (.01 to .27) of a standard deviation. There were no associations between dietary patterns in infancy and 4-year performance on the other tests. CONCLUSIONS: These findings suggest that dietary patterns in early life may have some effect on cognitive development. It is also possible that they reflect the influence of unmeasured confounding factors.